Diet quality among mothers and children in India: Roles of social and behavior change communication and nutrition-sensitive social protection programs - Nguyen, Phuong Hong; Neupane, Sumanta; Pant, Anjali; Avula, Rasmi; Herforth, Anna (Elsevier, 2024)
Background: Limited evidence exists on determinants of maternal and child diet quality.